Revolutionizing bone regeneration and wound healing: Mechanical stromal vascular fraction and hyaluronic acid in a mouse calvarial defect model - Ossanna, Riccardo; Quintero Sierra, Lindsey Alejandra; Ghazanfar Tehrani, Sara; Jha, Vivekanand; Curatola, Chiara; Busato, Alice; Conti, Anita; Conti, Giamaica; Zingaretti, Nicola; Parodi, Pier Camillo; De Francesco, Francesco; Riccio, Michele; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe stromal vascular fraction (SVF) is a complex and heterogeneous suspension derived from adipose tissue, containing both cellular and noncellular components. Its cellular fraction includes adipose-derived stem cells (ASCs), endothelial precursor cells, pericytes, macrophages, lymphocytes, and smooth muscle cells. The acellular “secretome” of SVF includes bioactive molecules such as growth factors, cytokines, chemokines, extracellular vesicles, and fragments of extracellular matrix (ECM), which contribute to its regenerative potential. Bone defeatures can be stimulated by mesenchymal stem cells (MSCs) that differentiate into osteoblast to support the healing and repair process. In addition to its cell content, the SVF is rich in growth factors, cytokines and chemokines, extracellular vesicles, and extracellular matrix components, which could stimulate regenerative processes through a trophic effect. Studies showed that hyaluronic acids are usually involved in healing processes. This study was focused on the healing potency of stromal stem cells isolated from adipose tissues by mechanical digestion, and the role of low-molecular-weight hyaluronic acid (LMW-HA, ACP) in the healing process was tested in calvarial defeatures in a mouse model, in comparison with the enzymatic digestion method.MethodsThe bone healing and remodeling process was evaluated in vivo using magnetic resonance imaging (MRI) up to 15 days post-treatment, and differences in the quality of bone regeneration were assessed by ex vivo histological analysis, immunofluorescences, and ultrastructural analysis. The bone matrix formed after treatment with mechanically digested Hy tissue stromal vascular fraction + hyaluronic acid (HT-SVF + ACP) was compared to that formed with enzymatically digested stromal vascular fraction + hyaluronic acid (ED-SVF + ACP), with the saline group serving as the control group.ResultsIn this study, we explore a groundbreaking approach using HT-SVF combined with ACP to promote bone regeneration. Through comparative analysis with ED-SVF in a calvarial defect mouse model, we demonstrate the superior efficacy of HT-SVF + ACP in enhancing bone healing, reducing fibrotic tissue, and improving bone matrix maturity.DiscussionThe findings establish the potential of HT-SVF as a cost-effective and efficient method for bone regenerative therapy.